Correcting students’ written grammatical errors: The effects of negotiated versus nonnegotiated feedback - Nassaji, Hossein (Studies in Second Language Learning and Teaching, 2011)
A substantial number of studies have examined the effects of grammar correction on second language (L2) written errors. However, most of the existing research has involved unidirectional written feedback. This classroom-based study examined the effects of oral negotiation in addressing L2 written errors. Data were collected in two intermediate adult English as a second language classes. Three types of feedback were compared: nonnegotiated direct reformulation, feedback with limited negotiation (i.e., prompt + reformulation) and feedback with negotiation. The linguistic targets chosen were the two most common grammatical errors in English: articles and prepositions. The effects of feedback were measured by means of learner-specific error identification/correction tasks administered three days, and again ten days, after the treatment. The results showed an overall advantage for feedback that involved negotiation. However, a comparison of data per error types showed that the differential effects of feedback types were mainly apparent for article errors rather than preposition errors. These results suggest that while negotiated feedback may play an important role in addressing L2 written errors, the degree of its effects may differ for different linguistic targets.